Meca para o turismo de negócios e eventos - Serson, Júlio (Revista Turismo em Análise, 1993)
The text focuses on the Importance of international tourism and tourism in Brazil, based on data from the World Tourism Organization (WTO) and the World Travel and Tourism Council (WITC). It discusses, especifically, tourism issues in the city of São Paulo, stressing its potentiality as a business and convention tourist destination. To achieve that goal, it is necessary to formulate a tourism promotion program, which could be strategically placed in two emission markets - the "southern cone" (Argentina, Paraguay and Uruguay) and Japan - in addiction to the enlarging of the São Paulo Convention and Visitors Bureau strategies and the combined action of public and private sectors.